Radiofrequency ablation of osteoid osteoma in common and technically challenging locations in pediatric population - Shaileshkumar Garge (Indian Journal of Radiology and Imaging, 2017)
Context: Percutaneous radiofrequency ablation (RFA) of osteoid osteoma has a high technical and clinical success rate. However, there is limited data on its use in the pediatric population, especially in technically challenging locations. Objective: To assess the safety and efficacy of computed tomography (CT)-guided percutaneous RFA of osteoid osteoma in pediatric population. Patients and Methods: From June 2009 to May 2014, 30 patients with osteoid osteoma were treated with CT-guided RFA in common (25 cases) and technically challenging (five cases: four near articular surface and one in sacrum) locations. Therapy was performed under general anesthesia with a three-array expandable RF probe for 6 min at 90°C and power of 60–100 W. The patients were discharged next day under instruction. The treatment success was evaluated in terms of pain relief before and after (1 day, 1 month, and 6 months) treatment. Results: Technical success was achieved in all patients (100%). Primary clinical success was 96.66% (29 of total 30 patients), despite the pediatric population and atypical location. One patient had persistent pain after 1 month and was treated successfully with a second procedure (secondary success rate was 100%). One patient had immediate complication of weakness of right hand and fingers extension. No delayed complications were observed. Conclusions: CT-guided RFA is relatively safe and highly effective for treatment of osteoid osteoma in pediatric population, even in technically difficult locations.